Embryonic Development of Bryconamericus caucanus (Characidae: Tetragonpterinae) under Laboratory Conditions (2010)
ABSTRACT: In this study we describe the early stages of development of Bryconamericus caucanus under laboratory conditions. Mature females (mean weight 8.12 g) received two intraperitoneal doses of Carp Pituitary Extract (1st dose of 0.5 mg / kg at time 0 and 2nd dose of 5 mg / kg 12 h later), and mature males received a single dose of 0.5 mg / kg at the time of the 2nd dose to the females. Extrusion of eggs was performed at 152.25 Accumulated Thermal Units. Eggs of B. caucanus were yellow, round shaped, non-adhesive, and the perivitelline space after hydratation was moderate. Hatching occurred 28 h 20 min after fertilization (21oC, 594.3 Accumulated Thermal Units). The morphological features of the egg and early embryo of B. caucanus were similar to previous reports in other members of the Tetragonopterinae, but the embryonic development was particularly long in this species